Physical and chemical stability of cytarabine in polypropylene syringes. (June 2021) - Ayed, Wiem Ben; Drira, Chema; Soussi, Mohamed Ali; Ouesleti, Hanen; Hamdene, Besma; Khrouf, Myriam; Safta, Fathi; Fradi, Ines
Background: Cytarabine is widely used to treat leukemia and lymphoma. Currently, Cyrabol®, powder for injection, is one of the specialties marketed in Tunisia. However, no stability data when diluted with 0.9% NaCl are available. The aim of this study is to evaluate the physical and chemical stability of cytarabine (Cyrabol®) solution after dilution in 0.9% NaCl (1 mg/mL, 5 mg/mL and 10 mg/mL) in polypropylene syringes under different storage conditions. Methods: Cytarabine solutions (1 mg/mL, 5 mg/mL and 10 mg/mL) in 0.9% NaCl were prepared in polypropylene syringes and stored for 28 days under different conditions. Cytarabine preparations in glass containers were prepared as a control to detect any adsorption. Chemical stability was assessed by a stability-indicating high-performance liquid chromatography method. The stability-indicating capacity of the method was proved by forced degradation tests. Linearity, precision and limit of detection and quantification were performed according to the International Conference on Harmonisation recommendations. Physical stability was checked by visual inspection. Results: The method was proven to be a validated stability-indicating assay. At 2–8°C, all tested solutions were chemically stable for 28 days. However, at 25°C, the main degradation product gradually increased during the study and the chemical stability of 1 mg/mL, 5 mg/mL and 10 mg/mL solutions was 14 days, 8 days and 5 days, respectively. Similar results were observed in the glass containers. Conclusion: The highest physical and chemical stability of cytarabine diluted in 0.9% NaCl in polypropylene syringes was observed at 2–8°C. At 25°C, better stability was found in the 1 mg/mL solution compared with those at higher concentrations (5 mg/mL and 10 mg/mL).